Minimization of Interchannel Interference E ects in Nyquist-WDM Systems (2017)
ABSTRACT: The need of increasing the capacity of current deployed optical networks to perform terabits transmissions has been driven to the development of superchannel systems, (principally based on Nyquist-WDM) to be carried out in flexible grid or gridless scenarios. Nevertheless, one of the main issues to be mitigated in these systems is the interchannel interference (ICI), whose effect is intensified when the spectral channel spacing is reduced (for further spectral efficiency increment). In this thesis, we present a study of the ICI effects in Nyquist-WDM systems by means of BER calculation as a function of several system parameters such as: frequency channel spacing, roll-off factor of the digital pulse-shaping filter, laser's linewidth, transmission distance, mark probability of the pseudo-random bit sequence, optical-to-signal noise ratio, among others. Besides, two methods enabling ICI mitigation are proposed: on one hand, a method based on FEC-coded sequence distribution among optical carriers for applications of multiple carriers (superchannels) as a single entity, and on the other hand, a method to perform nonsymmetrical demodulation (NSD) based on the k-means algorithm enabling time-varying distortions mitigation. In contradiction of techniques for ICI mitigation in recent art, these proposals avoid the use of multiple-input multiple-output equalizers or training sequences. Specifically, for NSD approach, information of adjacent channels is not required.